A concrete introduction to real analysis - Carlson, Robert, 1951- (Chapman and Hall/CRC, 2017)
The Second Edition offers a major re-organization of the book, with the goal of making it much more competitive as a text for students. The revised edition will be appropriate for a one- or two-semester introductory real analysis course. Like the first edition, the primary audience is the large collection of students who will never take a graduate level analysis course. The choice of topics and level of coverage is suitable for future high school teachers, and for students who will become engineers or other professionals needing a sound working knowledge of undergraduate mathematics.
OCLC-licensed vendor bibliographic record.
Keywords: Mathematical analysis